Análisis y Diseño de bases de columnas de acero - Sue, Rickford (Universidad Central "Marta Abreu" de las Villas, 2009)
This project presents the results obtained from the numerical modeling of steel column base plates, with the purpose of finding its behavior under the effect of the acting loads. This project contains a compilation of existing information on the design of base plates for steel columns. The project comprises of four chapters. Chapter I include material taken from reports, papers, texts and design guides. Chapter II consists of a summary of the different available design methods (Principally those of the Spanish, Russians and Americans). It explains the standard design spreadsheets developed in this chapter, explains the design concepts behind each procedure. Chapter III provides illustrative solved numerical examples which implement the use of Computer Assisted Design (CAD), (Mathcad 14, and EXCEL) in determining the answer of the relating elements, obtaining results closer to its true behavior. Chapter IV consists of creating and analyzing a simple model of the column base plate in the software ABAQUS 6.6-1, from which it is possible to deduce the real behavior of the element in question and therefore makes it feasible to conclude on the best design method according to the obtained results. The base plate in this report includes both an axial load and a moment. This kind of connection would be used at the base of moment resistant frames where moment capacity is needed. It is also used where the load is applied eccentrically to the column and the resulting moment must be resisted by the base connection. If the moment is relatively small, the connection can be designed without the use of anchor bolts, other than those provided for stability during construction. The more common case involves the use of one or more bolts to resist the tension resultant from the moment. The intent is to provide engineers with the research background and an understanding of the behavior of base plates and then to present information and guidelines for their design. The material is intended for the design of column base plates in building frames, though it can be used for related structures.
Keywords: Bases de Columna de Acero; Software ABAQUS 6.6-1